Respuesta :
The correct answer is choice 4.
You can factor f(x) to 6x^2(2x^3+6x^2-x)
Divide that by 6x^2 and you get choice 4.
You can factor f(x) to 6x^2(2x^3+6x^2-x)
Divide that by 6x^2 and you get choice 4.
For this case we have the following functions:
[tex]f (x) = 12x ^ 5-36x ^ 4-6x ^ 3\\g (x) = 6x ^ 2[/tex]
We must find the value of: [tex]\frac {f (x)} {g (x)}[/tex], then:
[tex]\frac {f (x)} {g (x)} = \frac {12x ^ 5-36x ^ 4-6x ^ 3} {6x ^ 2} = \frac {12x ^ 5} {6x ^ 2} - \frac {36x ^ 4} {6x ^ 2} - \frac {6x ^ 3} {6x ^ 2}[/tex]
For division of powers of the same base, the same base is placed and the exponents are subtracted:
[tex]\frac {f (x)} {g (x)} = 2x ^ 3-6x ^ 2-x[/tex]
Answer:
Option D